Perbedaan Status Gingiva Vegetarian dan Non-Vegetarian - Samatha Amelia Putri; Abdul Gani Soulisa (Jurnal Kedokteran Gigi Terpadu, 2019)
Background: Vegetarian is defined as a group of people who only eat plant foods and does not include meat, fowl, seafood, and processed products. According to the Indonesia Vegetarian Society (IVS), the number of vegetarians within this decade has increased significantly, and it has reached 60.000 people by 2007. The differences between vegetarian and non-vegetarian are on its consumption of animal’s products and the proportion of plant foods intakes. Fibers in vegetables and fruits can function as a natural toothbrush and stimulate saliva secretion. It can help in cleaning particles from the teeth surface during the process of chewing. The variance of dietary practices among vegetarian and non-vegetarian will make some differences in the individual assessment of dietary adequacy essential that may provide different nutritional status and health benefits. Objective: The purpose of this study was to observe the gingival status differences between vegetarian and non-vegetarian. Method: This study is an observational analytic comparison with cross-sectional study design. This study was conducted at the RSGM FKG USAKTI on October-November 2016. A total of 28 samples according to the inclusion and exclusion criteria divided into two groups (14 vegetarians and 14 non-vegetarians). The gingival status was assessed by using the Papilla Bleeding Index (PBI) and Interdental Hygiene Index (HYG). Result: The result of the Mann-Whitney test showed that there is no PBI and HYG differences between vegetarian and non-vegetarian (p > 0.05). Conclusion: In conclusion, gingival status was not significantly different between vegetarian and non-vegetarian.